TEKNIK BEDAH DENGAN SKALPEL PADA HIPERPIGMENTASI GINGIVA - Ade Ismail Abdul Kodir (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Gingival pigmentation is the coloring/staining of the gingiva in the form of a dark purplish color or irregular light brown spots. This staining is derived from melanin granules produced by cells melanoblas. Gingival hyperpigmentation caused by excessive melanin deposition . The cause of this gingival hyperpigmentation is multifactorial : genetic factors , local and systemic . The aims of this article is to overbear the gingival hyperpigmentation with simple techniques , does not require several equipments , but gives contentment results to the patient . Discussion : The gingival melanin hyperpigmentation is not cause medical problems , usually to the point the appearance especially when talking and smiling . Depigmentation is periodontal plastic surgery to remove or reduce gingival hyperpigmentation . There are many ways to eliminate gingival hyperpigmentation , one of them is a surgical using scalpel . Depigmentation surgery does not require any special tools but gives satisfactory results for the patient. Conclusion : Hyperpigmentation gingival surgery techniques can be overcome by using scalpel surgery.